Passenger Loyalty and Satisfaction: Empirical Evidence at the South Sumatra LRT Station in Indonesia - Ricardianto, Prasadja; Risdiana, Azis Okta; Abdurachman, Edi; Saputro, Soemino Eko; Purba, Okin Ringan (Universitas Mercu Buana, 2024)
During its operation, Light Rail Transit in the Province of South Sumatera had not become the main choice of transportation for people in Palembang and its surroundings. Objectives: This research aimed to analyze the direct and indirect influences of operational performance and service quality on passenger loyalty mediated by Light Rail Transit passenger satisfaction.Methodology: This research took the sample of all employees of the Station and passengers of Light Rail Transit Palembang as many as 100 people. The method of data analysis used in this research was the Path Analysis method.Finding: The research found that operational performance and service quality had positive and significant direct and indirect influences on passenger satisfaction and passenger loyalty, also passenger satisfaction had a positive and significant influence on passenger loyalty.Conclusion: Maintaining passenger loyalty needs an improvement in operational performance and service quality to achieve passenger satisfaction through the improvement of inter-division coordination and training. The improvement of operational performance and support from service quality will enhance passenger trust which, in turn, will increase the loyalty of LRT passengers.